2008
DOI: 10.1007/s12185-008-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-myeloma effect of homoharringtonine with concomitant targeting of the myeloma-promoting molecules, Mcl-1, XIAP, and β-catenin

Abstract: Since a variety of cell intrinsic and extrinsic molecular abnormalities cooperatively promote tumor formation in multiple myeloma (MM), therapeutic approaches that concomitantly target more than one molecule are increasingly attractive. We herein demonstrate the anti-myeloma effect of a cephalotaxus alkaloid, homoharringtonine (HHT), an inhibitor of protein synthesis, through the induction of apoptosis. HHT significantly reduced Mcl-1, a crucial protein involved in myeloma cell survival, in all three myeloma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…However, our data showed that the levels of Bim were unperturbed after HHT treatment (Figs. 3C and 2D), which are consistent with the studies described by Kuroda et al (40) who showed that HHT exerts a minimal effect on Bim expression in myeloma cells. These data from us and others argue against the possibility that HHT-induced apoptosis stems from upregulation of Bim.…”
Section: Hht Induces Apoptosis In D816v Kit-expressing Cells and Decrsupporting
confidence: 91%
“…However, our data showed that the levels of Bim were unperturbed after HHT treatment (Figs. 3C and 2D), which are consistent with the studies described by Kuroda et al (40) who showed that HHT exerts a minimal effect on Bim expression in myeloma cells. These data from us and others argue against the possibility that HHT-induced apoptosis stems from upregulation of Bim.…”
Section: Hht Induces Apoptosis In D816v Kit-expressing Cells and Decrsupporting
confidence: 91%
“…17 The IM9 subline with lower sensitivity to bortezomib (Bor) (IM9-Bor), established by Dr Terui Y, was maintained with 20 nM Bor. The recombinant hGal9, which is highly stable against proteolysis, was synthesized by Galpharma (Kagawa, Japan).…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…53 However, other reports have indicated that the proapoptotic activity of HHT may involve not only the activation of caspase-9, caspase-3, and PARP but also the activation of caspase-8, thus involving both intrinsic and extrinsic apoptotic pathways, as demonstrated in human myeloma cell lines and tumor cells from patients with recurrent/refractory multiple myeloma. 54,55 These discrepancies in the mechanism of action of HHT may relate to differences between omacetaxine and HHT as well as the use of different cell types in different reports. Mcl-1 down-regulation may result in an increase in free BH3-only proteins, such as Bim, tBid, Bik, and Puma in addition to reducing the levels of beta-catenin and X-linked inhibitor of apoptosis (XIAP) proteins.…”
Section: Phase 2 Studies Of Intravenous Hht In CMLmentioning
confidence: 99%